Effect Times Number of Spray and Concentration of Foliar Fertilizer (PIO20) in Growth and Yield of Cucumber Variety Jamila Planted in Plastic Houses Conditions (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The experiment was conducted during a season of 2016 in plastic houses at Azawia- Babylon to study effect times number of spray (two times،  three times ) with four levels of spray by foliar nutrition  PIO20 (0 ،1.5 ، 2 ،2.5 ml. liter-1) in cucumber plant c.v. jamila. The experiment was conducted of factorial in design using (C.R.D) with three replicates. Results showed the treatment spray of three times significantly on the treatment spray two times when imported  plant length rate (291.4) cm ,the number of leaves (36.63) leaf and dry weight of the shoot (25.76) gm , fruit long (17.98) cm , fruit weight (109.27) gm and the number of fruits (11.80) fruit.plant-1 and the one plant yield (1.294)kg. the results also showed all the treatment of spray significantly in vegetative growth and fruiting characteristics as compared with control treatment. the results of the interaction the significant superiority of the treatment spray of three times on the level 2 ml. liter-1 plant length rate (311.3) cm ,the number of leaves (40.71) leaf and dry weight of the shoot (32.09) gm , fruit long (19.34) cm , fruit weight (116.06) gm and the number of fruits (12.97) fruit.plant-1 and the one plant yield (1.506)kg.